Prevalence of Toxoplasma gondii, Neospora caninum, and Sarcocystis Species DNA in the Heart and Breast Muscles of Rock Pigeons (Columbia livia) - Muhammad Mudasser Nazir; Muhammad Mazhar Ayaz; Atif Nisar Ahmed; Azhar Maqbool; Kamran Ashraf; Muhammad Oneeb; Ghulam Yasin; Atta Subhani; Muhammad Asif Ali; Noman Nazir; Muhammad Afzal Sajid (Journal of Parasitology Research)
Little is known about the prevalence of protozoan parasites in the muscles of rock pigeons (Columbia livia). The muscles from 54 (heart from 45 and breast from 54) rock pigeons were examined for DNA of Toxoplasma gondii, Neospora caninum, and Sarcocystis species using PCR. Twenty-four were female and 30 were males. The birds were part of flocks of pigeons housed at the tombs of saints in Lahore, Pakistan. Birds that died or were euthanized due to poor health were submitted for necropsy at the Department of Parasitology, University of Veterinary and Animal Sciences, Lahore, Pakistan, where DNA isolations and PCR were conducted. Nineteen (35.1%) of the birds were positive for T. gondii DNA. Seven males and 12 females were positive. Breast tissue was always infected in T. gondii positive birds, while the heart was infected in 13 (28.8%) of breast positive birds. Five (9.2%) of the pigeons, 2 males and 3 females, were positive for N. caninum. The distribution of N. caninum DNA was more variable in the muscles of pigeons than T. gondii and was found only in the heart of 1 (female), heart and breast muscle of 2 (male), and only the breast muscle of 2 birds (female). One of the 54 rock pigeons (female) was positive for both T. gondii (heart and breast) and N. caninum (heart only). Two of the positive Neospora caninum amplicons were sequenced and had 97% nucleotide identity with N. caninum isolates. Sarcocystis DNA was not found in any bird. The prevalence of T. gondii in rock pigeons and their predation by cats suggest that they may play an unrecognized role in maintaining environmental contamination with T. gondii oocysts by cats. Our study indicates that rock pigeons are intermediate hosts of N. caninum and this information will aid in understanding the epidemiology of N. caninum.